Le paysagiste et l'écologue : comment obtenir une meilleure collaboration opérationnelle ? - Sylvain Morin; Sébastien Bonthoux; Philippe Clergeau (VertigO)
The need to take into account environmental and ecological issues in land use is highlighted in several political and legal texts. However, the implementation of biodiversity conservation objectives at the local level is still very light. The mere ecological approach would forget the relationship to the uses and ambiences that is the responsibility of the landscape design. In this article, we analyze the relationship between landscape designers and ecologists and make some proposals to improve the consideration of environmental issues and knowledge in development projects. First, it is necessary to break down barriers of landscape designer and ecologist cultures and to construct a dialogue in the different educations. The knowledge from researchers should be synthesized and made more affordable for practitioners. Landscape architects and ecologists should be more recognized by the contracting authority and integrated in local authority services. With the aim of creating multifunctional landscapes, it is essential to cross different intuitive, sensitive and scientific approaches and various tools throughout the project process. Finally, in order to capitalize on the knowledge developed during the project and make returns on experience, experimentation and evaluation phases could be developed during the design process.